2007
DOI: 10.1007/s00424-007-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of isometric and isotonic contractions during high-frequency stimulation

Abstract: Activity dependent potentiation is an enhanced contractile response resulting from previous contractile activity. It has been proposed that even a maximal effort contraction may be enhanced by prior activity if there is an increase in the peak rate of force development. This should increase the peak active force during a very brief maximal effort contraction. The purpose of these experiments was to evaluate potentiation during brief sequential contractions with high-frequency stimulation. For this experiment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…Important in this regard are studies by Grange et al [13,14] who showed that stimulation-induced elevations in RLC phosphorylation of mouse EDL muscle (in vitro, 25°C) were associated with greatly increased, i.e., 20-5% muscle work and power output during either zero load clamps, twitch after-loaded contractions and/or work cycles. Similarly, results obtained from rat skeletal hindlimb muscle studied in situ (37°C) by Abatte et al [1,2] and by MacIntosh and coworkers [24,25] demonstrate that the rate of work or power output measured during high-frequency activations was increased by 20-70% when proceeded by a conditioning stimulus that typically elevates RLC phosphorylation (to ∼0.50 mol phos per mole RLC). Taken together, these studies suggest that the RLC phosphorylation mechanism may, in addition to enhancing isometric properties, be particularly effective at potentiating dynamic aspects of skeletal muscle function.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Important in this regard are studies by Grange et al [13,14] who showed that stimulation-induced elevations in RLC phosphorylation of mouse EDL muscle (in vitro, 25°C) were associated with greatly increased, i.e., 20-5% muscle work and power output during either zero load clamps, twitch after-loaded contractions and/or work cycles. Similarly, results obtained from rat skeletal hindlimb muscle studied in situ (37°C) by Abatte et al [1,2] and by MacIntosh and coworkers [24,25] demonstrate that the rate of work or power output measured during high-frequency activations was increased by 20-70% when proceeded by a conditioning stimulus that typically elevates RLC phosphorylation (to ∼0.50 mol phos per mole RLC). Taken together, these studies suggest that the RLC phosphorylation mechanism may, in addition to enhancing isometric properties, be particularly effective at potentiating dynamic aspects of skeletal muscle function.…”
Section: Introductionmentioning
confidence: 55%
“…The muscle length as a fraction of optimal length (L/L o ) is displayed on the right vertical axis. The muscle lengths (as L/L o ) at which peak concentric twitch force was determined, and the corresponding stimulation phase (as%), were as follows 1.090 (−5), 1.075 (0), 1.060 (5), 1.045 (10), 1.030 (15), 1.015 (20), and 1.00 (25), respectively. Numbers in parentheses next to right axis show segment shortening speeds relative to maximum unloaded shortening velocity (1.00 V max ).…”
Section: Methodsmentioning
confidence: 99%
“…Using 200 Hz HFT stimulation in a different muscle, a previous investigation found a slightly faster normalized MRTD of 200 Hz isometric tetani at a 30°knee angle (short muscle length) compared to 60°or 90°(long) in the human knee extensors (de Ruiter et al 2004). However, post-activation potentiation also has a more pronounced affect at short compared to long muscle lengths (MacIntosh et al 2008;Pasquet et al 2005;Place et al 2005) and can increase the rate of torque development in the human quadriceps muscle even at very high firing frequencies of 400 Hz (MacIntosh et al 2008). In our study, length-dependent influences of postactivation potentiation might have been minimized because MRTD was always recorded from an evoked HFT train that immediately proceeded a *3-5 s conditioning isometric MVC.…”
Section: Contractile Slowing and Rommentioning
confidence: 84%
“…The most common indicator of PAP is increased evoked isometric twitch force (twitch potentiation) observed following an evoked isometric tetanic contraction (O'Leary et al 1997) or a maximal voluntary isometric contraction (MVC) (Vandervoort et al 1983). More relevant to performance of fast movements is that PAP increases the rate of force development of evoked isometric tetanic contractions (Baudry and Duchateau 2007a;MacIntosh et al 2008;Vandenboom et al 1995), the force and power of evoked high velocity shortening (concentric) contractions (Abbate et al 2000), and the maximum velocity attained by evoked shortening contractions under load (Baudry and Duchateau 2007b;MacIntosh et al 2008). In addition to its effects on evoked (involuntary) contractions, PAP has been associated with enhanced voluntary contraction performance such as increased isometric rate of force development (Baudry and Duchateau 2007a), increased torque of moderately high velocity isokinetic concentric contractions (Miyamoto et al 2010), and increased shortening velocity attained with various loads (Baudry and Duchateau 2007b).…”
Section: Introductionmentioning
confidence: 99%